Vowel Nasalization in the Hulu Pahang Dialect: (Penasalan Vokal dalam Dialek Melayu Hulu Pahang) (Jurnal Bahasa, 2019)
This article discusses a vowel nasalization phenomenon in Hulu Pahang Malay with attention to the Budu subdialect. The vowel nasalization in the area is deemed a unique phonological process due to (1) its limited distribution that can be found only in Budu (and adjacent villages), and (2) its sole occurrence concerning the vowel /a/ before final nasal. The question is, how does the Budu subdialect get this particular feature? Considering the limited distribution of areas and its restricted phonetic environments, assimilation is thus not a major factor in triggering the process. From the perspectives of diachronic dialectology and historical linguistics, the methodological approaches mainly focus on shared innovation and retention of certain linguistic features (e.g. Mahsun, 1995) and sociolinguistic typology (Trudgill, 2011). In order to reveal the sociolinguistic history of Budu society, this article suggests at least two possibilities that can be used as an explanation for the said phenomenon. The first possibility is dialect contact, and the second is the levels of innovation which occur in the history of the Budu subdialect and in the Hulu Pahang dialect, as well as all dialects in the eastern Peninsula (Semenanjung Timur). These possibilities are related to each other and needed to be analysed together. The findings show that the dialectal phenomena in the eastern parts of the Peninsula are highly mixed, in the sense that one dialect becomes a centre of diffusion, hence influencing the trajectory of innovation and retention of the other dialects..Keywords: nasalisation, dialectology, Hulu Pahang, Budu, dialects in contact